H3K27me3 forms BLOCs over silent genes and intergenic regions and specifies a histone banding pattern on a mouse autosomal chromosome - Pauler, Florian M.; Sloane, Mathew A.; Huang, Ru; Regha, Kakkad; Koerner, Martha V.; Tamir, Ido; Sommer, Andreas; Aszodi, Andras; Jenuwein, Thomas; Barlow, Denise P.

(untitled) (Genome Research, 2009)
In mammals, genome-wide chromatin maps and immunofluorescence studies show that broad domains of repressive histone modifications are present on pericentromeric and telomeric repeats and on the inactive X chromosome. However, only a few autosomal loci such as silent Hox gene clusters have been shown to lie in broad domains of repressive histone modifications. Here we present a ChIP-chip analysis of the repressive H3K27me3 histone modification along chr 17 in mouse embryonic fibroblast cells using an algorithm named broad local enrichments (BLOCs), which allows the identification of broad regions of histone modifications. Our results, confirmed by BLOC analysis of a whole genome ChIP-seq data set, show that the majority of H3K27me3 modifications form BLOCs rather than focal peaks. H3K27me3 BLOCs modify silent genes of all types, plus flanking intergenic regions and their distribution indicates a negative correlation between H3K27me3 and transcription. However, we also found that some nontranscribed gene-poor regions lack H3K27me3. We therefore performed a low-resolution analysis of whole mouse chr 17, which revealed that H3K27me3 is enriched in mega-base-pair-sized domains that are also enriched for genes, short interspersed elements (SINEs) and active histone modifications. These genic H3K27me3 domains alternate with similar-sized gene-poor domains. These are deficient in active histone modifications, as well as H3K27me3, but are enriched for long interspersed elements (LINEs) and long-terminal repeat (LTR) transposons and H3K9me3 and H4K20me3. Thus, an autosome can be seen to contain alternating chromatin bands that predominantly separate genes from one retrotransposon class, which could offer unique domains for the specific regulation of genes or the silencing of autonomous retrotransposons.